PENINGKATAN HOTS SISWA KELAS 4A MELALUI MODEL PEMBELAJARAN PBL MATA PELAJARAN IPAS DI MI NAHDLATUL ULAMA - Adillah, Farah; Amalia, Nur fitri (Universitas Islam Zainul Hasan Genggong, 2023)
This research aims to determine the increase in Higher Order Thinking Skills (HOTS) in science subjects through the Problem Basic Learning (PBL) learning model for class IV A MI Nahdlatul Ulama Kraksaan students. This research was conducted at MI Nahdlatul Ulama Kraksaan in the 2023/2024 academic year. This research is classroom action research with research procedures including planning, implementation, observation and reflection stages. The subjects of this research were all students in class IV A of MI Nahdlatul Ulama Kraksaan, totaling 28 students consisting of 17 male students and 11 female students. The object of this research is the application of the Problem Basic Learning learning model to improve Higher Order Thinking Skills (HOTS). The data collection techniques used are tests, observation, interviews and documentation. Data analysis was obtained by calculating the percentage of students passing high-level thinking skills. The results of the research showed that there was an increase in Higher Level Thinking Skills in the science and science subjects of class IV A students at MI Nahdlatul Ulama Kraksaan. You can see the average improvement and graduation from cycle to cycle. In cycle I the score in the very good category was 21.4%. In cycle II the score in the very good category was 85.7%.